Pelatihan PELATIHAN MENGENAL FUROSHIKI KAIN PEMBUNGKUS TRADISIONAL DARI JEPANG YANG RAMAH LINGKUNGAN BAGI SISWA DI SMK KESEHATAN DAN PARIWISATA BANGKINANG: MENGENAL FUROSHIKI KAIN PEMBUNGKUS TRADISIONAL DARI JEPANG YANG RAMAH LINGKUNGAN BAGI SISWA DI SMK KESEHATAN DAN PARIWISATA BANGKINANG - Merri Silvia Basri; Putri Rahayuningtyas -; Intan Sur (Universitas Negeri Surabaya, 2022)
Abstract Furoshiki is one of the traditional Japanese culture which means the use of eco-friendly traditional cloth as wrapping. In everyday life, furoshiki are used to wrap things. In the era of globalization, furoshiki is useful to reduce the use of plastic. Therefore, it is necessary to hold workshops and mentoring in the use of furoshiki among young people, especially high school and vocational students. The workshop materials include, 1) Definition of furoshiki, 2) history and development of furoshiki, 3) Type of fabric, size and motif of furoshiki, 4) Price of furoshiki, 5) Benefits and techniques of making furoshiki. The method used in this workshop is the method of community education and training by means of lectures, discussions and mentoring. Participants are introduced and taught how to make furoshiki so that they can be useful in everyday life. This activity was quite successful when seen from the enthusiasm of the participants in participating in the workshop and indicated by the participant satisfaction questionnaire which touched the figure of 70%. With this workshop, it is hoped that the younger generation will be more concerned about the environment and add insight to the participants. The success of this activity is due to the good cooperation of members of the community service team with the Principal, Japanese language teacher and students of the Health and Tourism Vocational School, Bangkinang City, Riau. Keywords: furoshiki, eco-friendly wrapping cloth